Improvement of Visual and Spatial Conceptions in Students with Dyslexia - Tūbele, Sarmīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Article is devoted to reveal how to improve visual and spatial conceptions in students with dyslexia. Theoretical framework of notions is presented and some practical activities are revealed. Basic concepts of dyslexia are presented and significance of visual and spatial development is described. Some practical aspects are described and stated. There are offered correctional developmental action models and the principles of selection and use of the tasks. The continuity and gradual increase of the difficulty degree is essential for the success of the adjustment and achievement of sustainable results.The latest researches in the neuropsychology have made major contribution to the understanding of the visual-spatial development and its importance during the learning process of reading literacy.They also provide insight into the relationship with specific reading disabilities and justify the necessity and possibilities of correction of visual-spatial perception disorders and deficiencies.